Isolation of soil bacteria able to degrade the anthelminthic compound albendazole - Lagos,Stathis; Koutroutsiou,Kalliopi; Karpouzas,Dimitrios G. (PeerJ, 2023)
Anthelmintic (AHs) veterinary drugs constitute major environmental contaminants. The use of AH-contaminated fecal material as manures in agricultural settings constitutes their main route of environmental dispersal. Once in soils, these compounds induce toxic effects to soil fauna and soil microbiota, both having a pivotal role in soil ecosystem functioning. Therefore, it is necessary to identify mitigation strategies to restrict the environmental dispersal of AHs. Bioaugmentation of AH-contaminated manures or soils with specialized microbial inocula constitutes a promising remediation strategy. In the present study, we aimed to isolate microorganisms able to actively transform the most widely used benzimidazole anthelminthic albendazole (ABZ). Enrichment cultures in minimal growth media inoculated with a soil known to exhibit rapid degradation of ABZ led to the isolation of two bacterial cultures able to actively degrade ABZ. Two oxidative products of ABZ, ABZSO and ABZSO2, were detected at low amounts along its degradation. This suggested that the oxidation of ABZ is not a major transformation process in the isolated bacteria which most probably use other biotic pathways to degrade ABZ leading to the formation of products not monitored in this study. Full length sequencing of their 16S rRNA gene and phylogenetic analysis assigned both strains to the genus Acinetobacter. The sequences were submitted in GeneBank NCBI, database with the accession numbers OP604271 to OP604273. Further studies will employ omic tools to identify the full transformation pathway and the associated genetic network of Acinetobacter isolates, information that will unlock the potential use of these isolates in the bioaugmentation of contaminated manures.
Keywords: Albendazole; Microbial degradation; Acinetobacter sp.; Benzimidazole anthelminthics